2020
DOI: 10.1371/journal.pone.0228315
|View full text |Cite
|
Sign up to set email alerts
|

The effects of omega-3 fatty acids on diabetic nephropathy: A meta-analysis of randomized controlled trials

Abstract: Objective To evaluate the effects of omega-3 long-chain polyunsaturated fatty acids on proteinuria, estimated glomerular filtration rate (eGFR) and metabolic biomarkers among patients with diabetes. Study design Meta-analysis of randomized controlled clinical trials (RCTs). Setting & subjects Patients with diabetes. Selection criteria for studies We conducted electronic searches in PubMed, Embase and Cochrane Central Register of Controlled Trials from January 1960 to April 2019 to identify RCTs, which examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…PUFAs and their metabolites have yielded conflicting results in individuals with DKD [165][166][167] . Concerns also exist regarding the purity of such supplements and the potential risk of increasing LDL levels 168 .…”
Section: Spms In Metabolic and Kidney Diseasementioning
confidence: 99%
“…PUFAs and their metabolites have yielded conflicting results in individuals with DKD [165][166][167] . Concerns also exist regarding the purity of such supplements and the potential risk of increasing LDL levels 168 .…”
Section: Spms In Metabolic and Kidney Diseasementioning
confidence: 99%
“…Previous cross-sectional studies demonstrated that PUFA intake was associated with a lower odds ratio (OR) for the presence of diabetic retinopathy [54] and that linolenic acid intake was associated with lower odds of peripheral neuropathy [27]. A meta-analysis revealed that omega-3 fatty acid supplementation reduced the amount of proteinuria in individuals with type 2 diabetes [55]. For the cardiovascular risk, a few randomized controlled trials [56,57] and a meta-analysis [58] did not show a benefit of omega-3 PUFA, but the Japan EPA Lipid Intervention Study (JELIS) [59] and the Reduction of Cardiovascular Events with Icosapent Ethyl-Intervention Trial (REDUCE-IT) [60] have shown a benefit of omega-3 PUFA [60].…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Considering the high incidence of serious consequences when DN was progressed to end-stage, a great deal of interventions have been developed in order to effectively treat it when DN was identified at the early stage. [ 10 , 11 , 15 ] However, most of the interventions have not potential of preventing or reversing DN, so no optimal treatment option has been reported presently. [ 12 ] Although researchers and practitioners have also changed attentions from western medicine to traditional Chinese medicine, and a series of clinical studies and meta-analyses have also been performed to investigate the efficacy and safety of some Chinese medicines for the treatment of early DN, [ 6 , 14 , 15 ] it remains to be answered about optimal regime.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several treatment options such as renin-angiotensin system blockers [ 10 ] and omega-3 fatty acids [ 11 ] have been developed to reduce the progression of kidney damage and then reduce the occurrence of complications resulted from DN. [ 12 ] However, these regimes have not potential of preventing or reversing DN, [ 13 ] and some regimes have been reported to be associated with increased incidence of adverse events and serious complications.…”
Section: Introductionmentioning
confidence: 99%